2019
DOI: 10.1002/mds.27780
|View full text |Cite
|
Sign up to set email alerts
|

Subtle gait and balance impairments occur in idiopathic rapid eye movement sleep behavior disorder

Abstract: Background Although motor abnormalities have been flagged as potentially the most sensitive and specific clinical features for predicting the future progression to Parkinson's disease, little work has been done to characterize gait and balance impairments in idiopathic rapid eye movement sleep behavior disorder (iRBD). Objective The objective of this study was to quantitatively determine any static balance as well as gait impairments across the 5 independent domains of gait in polysomnography‐confirmed iRBD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 37 publications
6
37
0
Order By: Relevance
“…Based on a comparable quantitative analysis and almost 3 times greater pool of iRBD patients, we were not able to confirm the subtle gait abnormalities during dual‐tasking reported by Ehgoetz Martens and colleagues even though we investigated both motor and cognitive dual‐task conditions. In agreement with Ehgoetz Martens and colleagues, we did not uncover any significant differences in gait during regular walking in our iRBD cohort, which is in contrast to the previous study reporting numerous gait deficits during normal walking in 42 probable RBD patients and 492 controls . We also did not find any effect of interference between the single‐task and dual‐task test, which was not yet investigated.…”
Section: Gait Characteristics For Normal Walking Cognitive and Motormentioning
confidence: 61%
See 3 more Smart Citations
“…Based on a comparable quantitative analysis and almost 3 times greater pool of iRBD patients, we were not able to confirm the subtle gait abnormalities during dual‐tasking reported by Ehgoetz Martens and colleagues even though we investigated both motor and cognitive dual‐task conditions. In agreement with Ehgoetz Martens and colleagues, we did not uncover any significant differences in gait during regular walking in our iRBD cohort, which is in contrast to the previous study reporting numerous gait deficits during normal walking in 42 probable RBD patients and 492 controls . We also did not find any effect of interference between the single‐task and dual‐task test, which was not yet investigated.…”
Section: Gait Characteristics For Normal Walking Cognitive and Motormentioning
confidence: 61%
“…We read with great interest the article by Ehgoetz Martens and colleagues showing subtle gait differences in idiopathic rapid eye movement sleep behavior disorder (iRBD) patients under the fast‐paced and cognitive dual‐task conditions. Although the results appear to be promising, they are based on a relatively small sample of 24 iRBD patients compared with 14 healthy controls . In contrast, our data obtained in a larger population of iRBD patients do not confirm the findings of early gait abnormalities.…”
Section: Gait Characteristics For Normal Walking Cognitive and Motormentioning
confidence: 99%
See 2 more Smart Citations
“…This relationship between pRBD and cognitive/motor function is potentially modified by an individual's educational level. The association between RBD, cognitive deficits, and motor abnormalities has been well-recognized, but previous studies mostly focused on PSG-confirmed RBD cases in clinical settings (25)(26)(27). However, RBD patients in clinical settings could have a more severe form of RBD, hence could present entirely different characteristics from the general population, which has been least studied.…”
Section: Discussionmentioning
confidence: 99%